The Impact of Capital Structure, Company Size, and Audit Opinions on Financial Reporting Timeliness: A Comparative Study Before and During the COVID-19 Pandemic - Ariandy, Christina Novita; Mappayunki, Ratna (Business, Management & Accounting Journal (BISMA), 2024)
This study aims to analyze the effect of capital structure and company size on the timeliness of financial reporting in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during 2017-2021, with audit opinion as a moderating variable. This study raises the main problem related to how much influence capital structure and company size have on the timeliness of financial reporting and how audit opinion can strengthen this relationship, both before and during the COVID-19 pandemic. The research method used is quantitative with a binary logistic regression and least squares approach. Secondary data were collected from 30 companies with a total of 150 observations. The study results show that before the COVID-19 pandemic, capital structure significantly affected the timeliness of financial reporting. In contrast, company size did not show a significant effect. The audit opinion has been proven to strengthen the relationship between capital structure and reporting timeliness. However, during the pandemic, neither capital structure nor audit opinion had a significant effect, while company size remained unaffected. The implications of this study provide new insights into the importance of considering the role of audit opinion in maintaining the timeliness of financial reporting, especially in crisis conditions such as a pandemic. The novelty of this research lies in the comparative analysis between the periods before and during the COVID-19 pandemic, which reveals the dynamics of the influence of capital structure and company size on the timeliness of financial reporting.